Broadbanding of a Gyro-TWT by dielectric-loading through dispersion shaping - Rao S.J.; Jain P.K.; Basu B.N. (My University, 2025)
A general cylindrical waveguiding interaction structure with a dielectric rod at its axis and a dielectric lining at its wall is field-analyzed to obtain a cold dispersion relation. The results of the cold analysis are combined with the hot dispersion relation of a dielectric-free gyro-traveling-wave tube (TWT) to obtain the hot dispersion relation of the dielectric-loaded gyro-TWT. The dispersion relation is interpreted to obtain the conventional TWT-type, Pierce-form gain equation. The dielectric parameters are chosen for a wideband coalescence between the beam and the waveguide modes. For a TE0n-mode gyro-TWT, the fundamental mode of operation (n = s = 1, where s is the beam-harmonic mode number), gives a higher gain which reduces as one goes for higher values of n = s. The second harmonic operation (n = s = 2), however, gives a larger bandwidth. The present analysis also suggests a method to select the values of the hollow beam radius relative to the waveguide wall radius for enhancing both the device gain and bandwidth. This study shows the feasibility of a wideband amplification in a gyro-TWT using dielectric loading, at higher gain values than those obtainable from other broadbanding schemes such as simultaneous profiling of the waveguide cross section and the background dc magnetic flux density. © 1996 IEEE.